2012
DOI: 10.1016/j.cell.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2 Binds to 5hmC Enriched within Active Genes and Accessible Chromatin in the Nervous System

Abstract: The high level of 5-hydroxymethylcytosine (5hmC) present in neuronal genomes suggests that mechanisms interpreting 5hmC in the central nervous system (CNS) may differ from those present in embryonic stem cells. Here we present quantitative, genome-wide analysis of 5hmC, 5-methylcytosine (5mC) and gene expression in differentiated CNS cell types in vivo. We report that 5hmC is enriched in active genes, and that surprisingly strong depletion of 5mC is observed over these regions. The contribution of these epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

57
797
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 840 publications
(880 citation statements)
references
References 54 publications
57
797
6
1
Order By: Relevance
“…Recent in vivo studies in the adult mouse brain confirm the preference of MeCP2 for mCG over nonmethylated CG, although MeCP2 clearly binds widely across the entire genome (11). Other studies have observed that MeCP2 binds to nonspecific DNA elements via its A/T hooks and basic and disordered protein domains, as well as to mCH, although the functional relevance of these interactions has not been explored (12)(13)(14)(15)(16). Given that MeCP2 levels rise in mammalian neurons for some time after birth (11,17) and approach those of the histone-octamer in the adult mouse brain (11), its differential binding to other DNA elements besides mCG is expected but has not yet been defined experimentally at high resolution.…”
mentioning
confidence: 90%
“…Recent in vivo studies in the adult mouse brain confirm the preference of MeCP2 for mCG over nonmethylated CG, although MeCP2 clearly binds widely across the entire genome (11). Other studies have observed that MeCP2 binds to nonspecific DNA elements via its A/T hooks and basic and disordered protein domains, as well as to mCH, although the functional relevance of these interactions has not been explored (12)(13)(14)(15)(16). Given that MeCP2 levels rise in mammalian neurons for some time after birth (11,17) and approach those of the histone-octamer in the adult mouse brain (11), its differential binding to other DNA elements besides mCG is expected but has not yet been defined experimentally at high resolution.…”
mentioning
confidence: 90%
“…MBD2 has a higher affinity to densely methylated CpGs than antibody-based approaches; therefore we may be missing single base pair differences. Conversely, MBD is able to discriminate between 5′ hydroxymethylcytosine and 5′ methylcytosine 24 with greater efficiency than the monoclonal antibody directed against 5-methylcytidine 64 . Regarding our sample selection, altered transcription is often used as a marker for astrocytic dysfunction 6, 9, 10 , however, astrocyte dysfunction can be defined in many ways and may not be reflected by gene expression differences.…”
Section: Discussionmentioning
confidence: 99%
“…The MBD2 protein specifically targets densely methylated CpGs 23 and does not target hydroxymethylated cytosines 23,24 thus sequencing MBD2-enriched DNA identifies methylated regions from the whole genome. Comparing the number of sequenced reads matching each region enabled us to identify methylation differences between cases and controls.…”
Section: Generation Of High Quality Genome-wide Mbd2-seq Profilesmentioning
confidence: 99%
“…Therefore, it is possible that the regulatory role of DNA methylation was mediated mainly by 5mC while 5hmC is just a byproduct of a leaky demethylation process. However, several recent studies suggest that 5hmC represents an transcription activating marker recruiting protein partners such as Mbd3/NURD complex and MeCP2 either preferentially or with equal affinity as 5mC 20,21 . Therefore, probably 5hmC is the genuine mediator of gene activation although it only occupies a small percentage of 5mC.…”
Section: Article Nature Communications | Doi: 101038/ncomms2995mentioning
confidence: 99%
“…5hmC probably exerts regulatory functions as a novel stable epigenetic modification as its content is hundreds-fold higher than 5fC and 5caC in different mouse organs 18,19 . Indeed, two recent studies showed that two methyl CpG binding proteins, MeCP2 and Mbd3, preferentially bind to 5hmC and may have important roles in transcription regulation 20,21 . Previous studies indicate that 5hmC is enriched in the exons of highly expressed genes in brain tissues, and in cis-regulatory elements such as active enhancers, insulatorbinding sites in ESCs [22][23][24][25][26][27][28] .…”
mentioning
confidence: 99%